The Sustainability Governance: Reciprocation Accountability based Emotional Quotient - Muhammad Wahyuddin Abdullah; Fetti Fatimah Yusuf; Andi Yustika Manrimawagau Bayan (Technium Social Sciences Journal, 2020)
The purpose of this research is to determine the application of reciprocation accountability which is accompanied by emotional quotient to be able to realize sustainable governance. This research is a qualitative study with a phenomenological approach. The results of this study showed that the existence of accountability at Wong Solo Restaurant is very appreciated by the leadership and the subordinates. The existing form of accountability is horizontally and vertically. In improving the accountability of reciprocation accountability leadership in carrying out its responsibilities need to have high emotional intelligence. The form of sustainability is same with good governance, transparency and accountability.